Isolation, Identification, and Antibacterial Assay of Indigenous Bacterial Isolates from Apis cerana Honeycomb - Simbolon, Kristina Br; Mokosuli, Yermia; Lawalata, Helen J (Universitas Labuhanbatu, 2023)
Apis cerana is a honey bee species with a cavity hive known as the eastern honey bee. Honey bee hives have Indigenous bacteria that have antimicrobial potential. Indigenous bacteria are free bacteria that can synthesize nitrogen compounds, sugars, and other bioactive substances. This study aims to isolate, identify and test the antibacterial of Indigenous bacteria isolate Apis cerana against gram-positive Staphylococus aureus and gram-negative bacteria Escherichia coli. This study used a descriptive research method to obtain the data from laboratory experiments. The study consisted of isolating Indigenous bacteria, identifying and testing the antibacterial agar diffusion method. The study results obtained seven isolates of AC 1, AC 2, AC 3, AC 4, AC 5, AC 6, AC 7 Indigenous bacteria from Apis cerana nests. AC 1 isolate has similarities with the genus Streptococcus, AC 2 isolates have similarities with the Klebsiella genus, while AC 3 isolates have similarities with the Bacillus genus, and AC 4, AC 5, AC 6 and AC 7 isolates have similarities with the Citrobacter genus. Indigenous bacterial isolates with potential antibacterial potential where the most significant inhibition against Staphylococus aureus bacteria was shown by isolate AC 1 (10.79 mm). At the same time, the smallest was found in isolate AC 7 (8.52 mm). The most significant inhibition against Escherichia coli bacteria was shown by isolate AC 1 (9.0 mm) while the smallest was found in isolate AC 3 (7.4 mm). Apis cerana nests have indigenous bacteria that have the potential to produce antibacterial substances